Rapid, directed transport of DC-SIGN clusters in the plasma membrane - Liu, Ping (Sci Adv, 2017)
C-type lectins, including dendritic cell–specific intercellular adhesion molecule-3–grabbing nonintegrin (DC-SIGN), are all-purpose pathogen receptors that exist in nanoclusters in plasma membranes of dendritic cells. A small fraction of these clusters, obvious from the videos, can undergo rapid, directed transport in the plane of the plasma membrane at average speeds of more than 1 μm/s in both dendritic cells and MX DC-SIGN murine fibroblasts ectopically expressing DC-SIGN. Surprisingly, instantaneous speeds can be considerably greater. In MX DC-SIGN cells, many cluster trajectories are colinear with microtubules that reside close to the ventral membrane, and the microtubule-depolymerizing drug, nocodazole, markedly reduced the areal density of directed movement trajectories, suggesting a microtubule motor–driven transport mechanism; by contrast, latrunculin A, which affects the actin network, did not depress this movement. Rapid, retrograde movement of DC-SIGN may be an efficient mechanism for bringing bound pathogen on the leading edge and projections of dendritic cells to the perinuclear region for internalization and processing. Dengue virus bound to DC-SIGN on dendritic projections was rapidly transported toward the cell center. The existence of this movement within the plasma membrane points to an unexpected lateral transport mechanism in mammalian cells and challenges our current concepts of cortex-membrane interactions.